Investigating Students Perceptions to Blended Learning: A Mixed-Method Study in A Rural Area of Indonesia - Nurcahyoko, Kunto (English Language Education Study Program, 2023)
Blended learning environments have become increasingly popular in higher education institutions worldwide, including in Indonesia. However, little is known about the perceptions of university students towards blended learning in rural areas of Indonesia. This study aims to explore the perceptions of university students towards blended learning environments in a rural area of Indonesia. A mixed-methods approach was used to collect data from 23 university students through surveys and interviews in three categories: learning materials, assessments, and interactive activities. Results showed that the majority of students had a positive perception of blended learning, with the convenience of learning at their own pace being the most cited benefit. The most preferred multimedia learning material is the combination of verbal materials with visual materials (69.6%). In response to assessment type, the most preferred assessment for the students in blended learning is Asynchronous tests (65.2%). In response to the most preferred interaction and collaboration activities, a regular and external digital tool like WhatsApp (73.9%). Future research should explore the effectiveness of blended learning in improving learning outcomes in rural areas of Indonesia.